Extração/Purificação do composto ativo da semente da Moringa Oleifera Lam e sua utilização no tratamento de água para consumo humano - Madrona, Grasiele Scaramal (2010)
The careful monitoring of many indicators is necessary to guarantee good quality control in the process of obtaining drinking water, in particular for human consumption. The contamination of aquatic environments makes that process even more complex and important, motivating the development of innovative techniques. In that sense, the utilization of natural coagulants, in lieu of chemical coagulants, has advantages related to biodegradability properties, lower toxicity, and lower rates of residual sewage sludge. The extract of the Moringa oleífera Lam's seeds is a great option among the many natural coagulants since it contains a cationic protein with high molecular weight which destabilize the particles found in the water, allowing for its purification. Considering the high demand for quality water, the process of filtration employing membranes is also attractive because it is very efficient. Moreover, the utilization of combined processes such as coagulation/flocculation/sedimentation/filtration with membranes has been actively studied given its significant improvements in the quality of drinking water and reduction of the membrane clogging. In this context, this work aimed to evaluate the efficiency of the Moringa oleífera Lam's coagulant in the process of coagulation/flocculation/sedimentation followed by filtration with membranes in order to obtain drinking water. Different types of extraction were analyzed to get the active compound of the Moringa oleífera Lam's seeds, optimizing the step of coagulation/flocculation/sedimentation. After that, the ideal conditions found were used in the process of microfiltration utilizing 0.1 and 0.2 µm membranes with pressures of 1 and 2 bar. Filtration of raw water with membrane and no coagulant was also investigated. Finally, three analyses took place: a kinetic study in the process of coagulation/flocculation, an evaluation regarding the stability of the Moringa oleífera's seeds and extract in relation to the storage time on refrigeration temperature, and a mathematical examination of the experimental data obtained during the process of filtration with membranes. The obtained results produced show several interesting aspects as follow. The coagulation/flocculation/sedimentation process alone, without filtration, is inefficient as far as obtaining proper quality water. In general, a higher efficiency level of color, turbidity, and UV- 254 nm removal was associated with the extraction carried out using only the salt KCl in the cases of low color and turbidity water while waters containing high color and turbidity, the highest efficiency occurred with extraction utilizing water and KCl salt. The lowest rates of clogging happened in combined processes employing the extraction with saline solution. By means of the kinetic study, it was possible to observe that the longest half-lives were found when removing composites with absorption under UV-254 nm. Analyzing the seed stability in relation to the storage time, a reduction in coagulation power was noticed after one year. On the other hand, the extract got with water showed coagulating activity up to five days of storage, while the one obtained with saline (KCl) remained efficient for five month. In general, the predominant clogging type detected was the cake formation. Hence, this study concludes that the association of processes and application of the Moringa oleífera is a viable alternative for obtaining potable water.